Audit Quality Reduction Behavior: A Literature Review - Shachariyah, Nafachatus; Rochayatun, Sulis (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
Audit quality has become an important issue for accounting professionals. The phenomenon of audit quality criticism from stakeholders such as users of financial statements and the government who shows dissatisfaction with financial statements will pressure auditors to improve audit quality. Auditors do not always apply audit procedures in the audit program. Audit quality behavior is defined as the auditor's actions during the audit process by reducing the effectiveness of existing audit evidence. This study aims to discuss the behavior of audit quality reduction a review of the existing literature related to that issues and then identify empirical evidence from previous research. Data collection techniques through search in national and international journals and selected based on related keywords, audit quality reduction. Based on the results of previous research, it is known that time pressure, work-family conflict, high work stress levels, audit fees, and experience can affect the behavior of decreasing audit quality. In contrast, work-family conflict and experience have no significant effect. The implications of the results of this study are expected to provide an in-depth understanding of the factors that affect the reduction of audit quality so that it can be used as evaluation material to improve audit quality.